Adolescent Suicide- A Rising Trend - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2016)
Suicide has become one of the leading cause of death in adolecesnt age group. In this abstract we are trying to find out causes of increasing trends and preventive stratigies.